Recent Advances in Understanding of the Role of Synuclein Family Members in Health and Disease - Ninkina, Natalia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, we have compiled data and opinions from leading scientists to demonstrate the recent advances in the study of function and dysfunction of synucleins. These proteins are involved in multiple normal and pathological molecular processes and consequently have various effects on cell biology of the nervous system. Three members of the synuclein family share many structural properties and have an overlapping pattern of expression and intracellular distribution in the developing and adult nervous system, which point to functional redundancy within the family. However, each synuclein has its own functions which are not shared with the two other family members, and there are certain cellular mechanisms and pathways in which these functions could be antagonistic rather than synergistic.